Currency Boards : The Ultimate Fix? - Ghosh, Atish (IMF Working Papers; Working Paper, 1998)
The growing integration of world capital markets has made it fashionable to argue that only extreme exchange rate regimes are sustainable. Short of adopting a common currency, currency board arrangements represent the most extreme form of exchange rate peg. This paper compares the macroeconomic performance of countries with currency boards to those with other forms of pegged exchange rate regime. Currency boards are indeed associated with better inflation performance, even allowing for potential endogeneity of the choice of regime. Perhaps more surprisingly, this better inflation performance is accompanied by higher output growth.